Modeling the Performance of Dy3+‐Based Boltzmann Thermometers by the Judd–Ofelt Theory. Issue 6 (26th February 2022) - Martinović, Ana; Dramićanin, Miroslav D.; Ćirić, Aleksandar
Abstract: Energy level positions, refractive index values, Judd–Ofelt (JO) intensity parameters, Slater integrals, and spin‐orbit coupling parameters are taken from the literature for 27 Dy 3+ ‐doped materials (five crystals and 22 glasses). Investigated are only the transitions that are used for the Boltzmann‐type luminescence intensity ratio (LIR) thermometers (transitions from the three thermalized levels, 4 F9/2, 4 I15/2, and 4 G11/2 to the ground level). Reduced matrix elements of these three transitions are calculated from the Slater integrals and spin‐orbit coupling parameters and they are compared to the most frequently used values from Carnall's tables. The comparison of JO parameters shows the smaller variation of the Ω6, related to rigidity, in crystal hosts than in glasses, and the opposite was observed for the Ω2, 4 parameters. LIR performances are simulated by the JO thermometric model for each material by the conventional LIR and the LIR that exploits the third thermalized level. The comparison of the predicted figures of merit in luminescence thermometry reveals the most promising thermometric Dy 3+ doped crystals and glasses. Abstract : Judd–Ofelt parameters taken from the literature enable simulation of luminescence intensity ratio thermometric parameters and prediction of sensitivities. The model is applied to 27 Dy 3+  doped materials (crystals and glasses) for conventional luminescence intensity ratio method and by 3 rd thermalized level, allowing for selection of the best sensor material.